SEBOTOK WHARF CONSTRUCTION RISK MANAGEMENT ANALYSIS SUMBAWA WEST NUSA TENGGARA - Isra Junna (Jurnal Teknik Sipil dan Teknologi Konstruksi, 2023)
Abstract:   The construction of the Sebotok Pier in Sebotok Village, Labuhan Badas Subdistrict, was carried out for the 2017 Fiscal Year, with Contract Number 027/34/PPK-DISHUB/VIII/2017 dated 21 August 2017 with an implementation period of 125 calendar days (from 21 August to 23 December 2017) and maintenance period of 180 calendar days. Contract Addendum Number 027/63.1/PPK-DISHUB/XII/2017, December 11 2017 (August 21 to January 12 2018). The work was 100% complete and a Provisional Hand Over (PHO) was carried out on January 23 2018. Based on information that there was damage to the Causeway (collapse of the talud masonry wall) in March 2019 and repairs had been carried out in the same month. The Construction Experts Team aims to provide technical justification related to the Sebotok Wharf Construction work, Labuhan Badas District. Referring to the Decree of the Inspector of Sumbawa Regency Number 732.a.Year 2019 concerning the Appointment and Determination of the Amount of Honorarium for the Team of Construction Experts in the Investigation Audit of the Causeway Work for the Sebotok Wharf Development, Sumbawa Regency for the 2017 Fiscal Year addressed to the Team of Construction Experts. The Construction Expert Team conducts field data collection; measuring the dimensions of the causeway construction, checking the physical condition of the causeway building, taking material samples and laboratory tests, interviewing (village officials, community leaders, several people who were directly involved as workers in the implementation of the causeway construction) and documentation. From the results of the analysis it can be concluded that masonry construction in causeway work with dimensions of width (B) 0.40 m, and height (H) 2.16 m a stability safety score of <1.5 is obtained so that the construction is declared UNSAFE. Keywords: Justification, Wharf, Construction Services